Estimation of house price differential of urban tree cover: an application of sample selection approach. Issue 25 (28th May 2018) - Mei, Yingdan; Hite, Diane; Sohngen, Brent
ABSTRACT: Hedonic valuation of urban forest amenities tends to assume that these attributes are exogenous to sample selection, which might render the estimated results misleading. This article intends to estimate the house price differential of urban tree cover by considering the sample selection issue. The main hypothesis is that houses with high tree cover generates higher utility to consumers, and thus leads to higher house price, ceteris paribus . It may attribute to the fact that consumers self-select into purchasing houses with high- or low-density tree cover based on some unobserved systematically different characteristics. As a result, estimates from sample selection models confirm the hypothesis that purchasing a house with high-density tree cover leads to a positive price differential compared with the low-density tree cover in Napa, Los Angeles, and that buying a low-density tree cover house results in negative price differential in Napa, Los Angeles.